NEW METHODS OF TEACHING ENGLISH IN TECHNICAL DIRECTIONS (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The development of a didactically organized set of games is necessary, since the effectiveness of solving dissertation research problems depends on it. Selecting a set of games will make it possible to solve problems such as correcting errors and overcoming difficulties in the process of forming a communicative culture for students in grades 2-4.